Gender Distribution of Authors of Evaluation Letters for Promotion at One Medical School. (5th July 2022) - Logeais, Mary E.; Eckerstorfer, Margaret; Krohn, Kristina M.; Everson-Rose, Susan A.; Termuhlen, Amanda M.; Joseph, Anne M.
Abstract : Purpose: Women remain underrepresented in key leadership positions and advanced ranks in academic medicine. This study examines the numbers of men and women letter writers for promotion candidates during a 5-year period across departments, tracks, ranks, and candidate gender. Method: A descriptive study characterized the gender of evaluation letter writers for candidates for promotion to associate or full professor at the University of Minnesota Medical School between 2015 and 2020. Letter writer and candidate gender were characterized by self-identified pronouns in the faculty biography or dossier. Letter writer gender was described by candidate department, promotion track, rank, terminal degree, and gender. Results: Among 299 candidates for promotion, 172 (58%) were men and 127 (42%) were women; dossiers included 3, 995 evaluation letters. Across all years, men wrote more letters than women (external letters, range, 69% in 2019–2020 to 75% in 2015–2016; internal letters, range, 67% in 2018–2019 to 77% in 2015–2016). Candidates in the family medicine and pediatrics departments had the highest percentages of letters written by women (44% and 40%, respectively). No differences were found in the number of women letter writers by candidate promotion track; however, differences were found by candidate rank (associate professor, 30%; full professor, 23%) and terminal degree (MD/DO, 25%; PhD, 33%; MD–PhD, 20%). Regardless of candidate gender, most evaluation letters were written by men. Women candidates had 15% to 20% more letters authored by women than men candidates (34%–40% vs 18%–23%). Conclusions: The gender pattern of letter writers may reflect implicit biases regarding gender and perceived leadership status, expertise, and success. Adopting policies that promote or require gender diversity among letter writers for promotion candidates may provide an opportunity to encourage faculty to seek diverse networks and recognize the achievements of women faculty.